Incidence and predictors of left atrium thrombus in acute ischemic stroke patients without atrial fibrillation: a single center cohort study. (25th November 2020) - Cinar, T; Hayiroglu, M.I; Cicek, V; Asal, S; Atmaca, M.M; Keser, N; Orhan, A.L
Abstract: Introduction: The present study aimed to determine independent predictors of left atrial thrombus (LAT) in acute ischemic stroke patients without atrial fibrillation (AF) using transesophageal echocardiography (TEE). Material and methods: In this single center, retrospective cohort study, we enrolled 149 consecutive acute ischemic stroke patients. All of the patients underwent TEE examination to detect LAT within 10 days following admission. Multivariate logistic regression analysis was performed to assess independent predictors of LAT. Results: Among all cases, 14 patients (9.3%) had a diagnosis of LAT on TEE examination. In a multivariate analysis; a previous diagnosis of cerebrovascular accident, elevated mean platelet volume (MPV), low left ventricle ejection fraction (EF) and a reduced left atrium appendix (LAA) peak emptying velocity were independent predictors of LAT. The area of MPV under the receiver operating characteristic curve analysis was 0.70 (95% CI: 0.57–0.83; p=0.011). With the optimal cut-off value of 9.45, MPV had a sensitivity of 71.4% and a specificity of 63% to predict LAT. Conclusion: Patients with low ventricle EF and elevated MPV should undergo further TEE examination for the possibility of cardio-embolic source. In addition, this research may provide novel information with respect to the applicability of MPV to predict LAT in acute ischemic stroke patients without AF. Funding Acknowledgement: Type of funding source: None